Characteristics of Gut Microbiota in Patients With Clear Cell Renal Cell Carcinoma - Chen, Yang; Ma, Junjie; Dong, Yunze; Yang, Ziyu; Zhao, Na; Liu, Qian; Zhai, Wei; Zheng, Junhua (Frontiers in Microbiology, 2022)
Different gut microbiota are implicated in different diseases, including cancer. However, gut microbiota differences between individuals with clear cell renal cell carcinoma (ccRCC) and healthy individuals are unclear. Here, we analyzed gut microbiota composition in 51 ccRCC patients and 40 healthy controls using 16S rRNA sequencing analysis. We observed that Blautia, Streptococcus, [Ruminococcus] torques_group, Romboutsia, and [Eubacterium]_hallii_group were dominant and positively associated with ccRCC. To characterize specific gut microbiota promoting ccRCC, we isolated and cultured Streptococcus lutetiensis and showed it promoted in vitro ccRCC proliferation, migration, and invasion through TGF-β signaling pathway. Interactions identified between the gut microbiota and ccRCC suggest the gut microbiota could serve as a potentially noninvasive tool for predicting ccRCC risk and also function as a cancer therapy target.